Disease and prejudice: risk attribution to ethno-racial groups over the course of a pandemic - Tamara Bogatzki; Jana Catalina Glaese; Julia Stier (Journal of Ethnic and Migration Studies, 2024)
Past research suggests that disease outbreaks drive prejudice towards minorities as they increase economic and disease threats. Based on an open-ended survey question distributed to 7,902 German residents over the course of one year of the Covid-19 pandemic (April 2020 to April 2021), we investigate the link between life-threatening events and ethno-racial prejudice. We find that pandemic-related threats only drive respondents' tendency to scapegoat ethno-racial groups if they hold left and center leaning ideologies. However, for far-right supporters who are the most likely to attribute the spread of Covid-19 to ethno-racial groups, pandemic-related threats do not affect that attribution. We further find that threat theories are of limited relevance for explaining which ethno-racial groups are targeted: respondents held Chinese accountable at the beginning of the pandemic but quickly shifted their attention to immigrants – a salient figure in pre-Covid-19 rightist rhetoric. We show that ideology, more than pandemic-induced threat, continues to drive prejudice and demonstrate the under-utilized advantages of using open-ended survey questions for understanding the dynamics of intergroup prejudice.
Keywords: 320; COVID-19 pandemic; Race/ethnicity; Political ideology; Threat; Far-right